Kinerja Efisiensi Energi Terhadap Manajemen Biaya Operasional Gedung - Dano Quinta Revana; Wisnumurti Wisnumurti; Agung Murti Nugroho (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2018)
The concept of Green Building is one of the efforts to reduce the effects of global warming through developmental aspects. Excessive energy consumption becomes an issue of global warming and waste of operational cost in the building so that this research will conduct an assessment using GREENSHIP and SNI parameters in Building E Faculty of Administration Brawijaya University expected to know the level of